O atendimento pedagógico domiciliar de alunos que não podem frequentar fisicamente a escola: o caso do Distrito Federal - Salla, Helma (2017)
The purpose of this study was to contribute to the investigation of the Pedagogical Home Care (APD), from the perspective of the Inclusive School, prioritizing the aspects related to its effectiveness by means of the elaboration of a normative proposal directed to the Secretary of State for Education of the Federal District (SEEDF) and the school community. As this research took place in the context of a Professional Master's Degree, the focus was to develop a normative proposal to be presented to SEEDF as a possibility for the implementation of ODA within the scope of it. The references were the documents available on the website of SEEDF and EAPE, and the documents published by the Ministry of Education (MEC) regarding Inclusive Education, Guidance for Pedagogical and Hospital Attendance (BRASIL, 2002) and research Carried out in the area. We verified that, within the scope of the Secretariat, there is a need to make ODA effective for all students who need it, even if it is a law, it is also necessary to include the school with the health system, with the family and social assistance, The adequacy of the physical conditions, the integration of the student with the school, the adequacy of the materials and pedagogical attention, the importance of an integrated support network for the teacher is pointed out so that he can develop the pedagogical work.